A high-performance supercapacitor electrode based on N-doped porous graphene - Dai, Shuge; Liu, Zhen; Zhao, Bote; Zeng, Jianhuang; Hu, Hao; Zhang, Qiaobao; Chen, Dongchang; Qu, Chong; Dang, Dai; Liu, Meilin (Journal of power sources, 2018)
The development of high-performance supercapacitors (SCs) often faces some contradictory and competing requirements such as excellent rate capability, long cycling life, and high energy density. One effective strategy is to explore electrode materials of high capacitance, electrode architectures of fast charge and mass transfer, and electrolytes of wide voltage window. Here we report a facile and readily scalable strategy to produce high-performance N-doped graphene with a high specific capacitance (∼390 F g−1). A symmetric SC device with a wide voltage window of 3.5 V is also successfully fabricated based on the N-doped graphene electrode. More importantly, the as-assembled symmetric SC delivers a high energy density of 55 Wh kg−1 at a power density of 1800 W kg−1 while maintaining superior cycling life (retaining 96.6% of the initial capacitance after 20,000 cycles). Even at a power density as high as 8800 W kg−1, it still retains an energy density of 29 Wh kg−1, higher than those of previously reported graphene-based symmetric SCs. [Display omitted] •N-doped graphene with 3D porous architecture was successfully prepared.•The electrode delivered high specific capacitance and excellent cycling stability.•The symmetrical supercapacitor achieved a remarkable energy and power density.